2004
DOI: 10.1063/1.1825991
|View full text |Cite
|
Sign up to set email alerts
|

Vibrationally resolved rate coefficients and branching fractions in the dissociative recombination of O2+

Abstract: We have studied the dissociative recombination of the first three vibrational levels of O 2 ϩ in its electronic ground X 2 ⌸ g state. Absolute rate coefficients, cross sections, quantum yields and branching fractions have been determined in a merged-beam experiment in the heavy-ion storage ring, CRYRING, employing fragment imaging for the reaction dynamics. We present the absolute total rate coefficients as function of collision energies up to 0.4 eV for five different vibrational populations of the ion beam, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
46
0

Year Published

2008
2008
2015
2015

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 71 publications
(49 citation statements)
references
References 65 publications
3
46
0
Order By: Relevance
“…It is reasonable to assume T rot ≈ T vib = 300 K. Equation (4) be used to calculate the thermal rate constant for electron temperatures much higher than 300 K but one should note that the equation does not regard excitation of vibrational and rotational states of higher temperatures. However investigations of the dependence of DR rates on vibrational excitation in the case of O + 2 by Petrignani et al (2005) showed a change of much less than an order of magnitude.…”
Section: Cross Sections and Rate Constant Determinationmentioning
confidence: 99%
“…It is reasonable to assume T rot ≈ T vib = 300 K. Equation (4) be used to calculate the thermal rate constant for electron temperatures much higher than 300 K but one should note that the equation does not regard excitation of vibrational and rotational states of higher temperatures. However investigations of the dependence of DR rates on vibrational excitation in the case of O + 2 by Petrignani et al (2005) showed a change of much less than an order of magnitude.…”
Section: Cross Sections and Rate Constant Determinationmentioning
confidence: 99%
“…33, and references therein͒. Here, the matrix cage comes into play because the photoelectron clearly has an increased chance to recombine with O 2 + due to backscattering in the matrix.…”
Section: A General Remarksmentioning
confidence: 99%
“…The 1 ⌺ u + potential curve crosses with vibrational states of the molecular ion ͑ =1,2͒ at 12.4 eV and leads to the O͑ 1 S͒ and O͑ 1 D͒ states. 33 Dissociation along this pathway produces photofragments with a kinetic energy of Ϸ0.4 eV.…”
Section: A Coexpansion Experimentsmentioning
confidence: 99%
“…5) can be associated either to IDCE (a, b, c, e) or DDCE (d, f) [3,4,6]. Those processes are indicated below:…”
Section: Dr2013mentioning
confidence: 99%
“…Petrignani et al [3] have developed and characterized an electron impact source, which was installed at the CRYRING storage ring to study the vibrational dependence of the DR rate coefficient through a decomposition of the projected distance spectra recorded under different source conditions. In this paper an alternative method for the production of a rovibrationally selected beam of O + 2 is discussed, which relies on resonance enhanced multiphoton ionization (REMPI) of a gas jet in a dedicated laser ion source.…”
Section: Introductionmentioning
confidence: 99%